A Temporary Spire for Eternity The Buurtower of Utrecht (Bulletin KNOB, 2006)
The present Buurtower has a Romanesque predecessor, the foundations of which were excavated in 1933. The place of this disappeared tower is still recognizable. The tower used to stand to the east of the present one. In the present church nave its place can be recognized by the rhythmical interruption of the columns and a definitely larger vault panel. In 1370 the building of the present Gothic tower had started, but in 1380 it was interrupted when the tower structure had reached a height of 17 meters. This building freeze is still recognizable by the different use of the natural stones in the corners of the facade. For this building phase corner blocks of a light grey French limestone were used.During the following building phase a sandy limestone with its characteristic beige colour was used. After an approximately 14-year interval they started building again until the work on the unfinished lantern was ceased in 1405 and the tower was covered with a temporary eight-sided spire construction. This temporary, wooden eight-sided construction was cramped between the wall work of the unfinished lantern and covered up by the spire roof.In the complicated eight-sided construction space was created for the municipal banishment bell. The church bells were hung in a separate belfry in the tower structure. The banishment bell was used for announcing regulations, executions and banishments. During the 15th century the bell was recast a few times until in 1471 a bell maker called Steven Butendyc gave the bell its present shape. The eight-sided spire construction was not strong enough to cope with the ringing of this new and bigger pendulum bell and it showed constructive wear and tear. In 1477-1478 some parts of the eight-sided construction were removed to make room for the present belfry for the banishment bell.In about 1440 the spire was partially levelled to place a small lantern for the watch bell. In 1674 this lantern was damaged because of a storm that caused serious damage to many churches, towers and houses of the city of Utrecht. The Gothic lantern was replaced by the present lantern with a small cupola. The temporary eight-sided spire was preserved.Several times during the 18th and 19th century the city government tried to sell the banishment bell, to melt it down, and to demolish the tower with its temporary spire construction in order to save on the maintenance cost. So far the tower had survived once again, but in 1943 disaster struck when the German occupier seized the historical bells in order to use and recast them for the German war industry. Only the banishment bell stayed behind in the tower.Fortunately, the vanished historical bells were returned shortly after the war but weren't replaced in the Buurtower. They were given to neighbouring church towers whose bells had not been returned. Until in 2001 the lonely banishment bell was reunited with the vanished bells, when they were returned and replaced in the restored Buurtower.